A complementary density gradient of zwitterionic polymer brushes and NCAM peptides for selectively controlling directional migration of Schwann cells. (July 2015) - Ren, Tanchen; Yu, Shan; Mao, Zhengwei; Gao, Changyou
Abstract: Selective enhancement of directional migration of Schwann cells (SCs) over fibroblasts (FIBs) plays a significant role in peripheral nerve regeneration, because this behavior facilitates neuron repair and avoids fibrosis. Herein a complementary density gradient of poly(3-dimethyl-methacryloyloxyethyl ammonium propane sulfonate) (PDMAPS, a zwitterionic polymer with antifouling property) and KHIFSDDSSE peptide (KHI, derived from neural cell adhesion molecule NCAM which mediates cell–cell adhesion) was fabricated. The gradient was visualized by fluorescent labeling, and further characterized by X-ray photoelectron spectrometry (XPS) and quartz crystal microbalance with dissipation (QCM-d). The SCs exhibited preferential orientation and enhanced directional migration on the gradient surface toward the region of lower PDMAPS density and higher KHI peptide density, while FIBs showed random migration. Moreover, the migration rate of the SCs was significantly enhanced to 2 folds, whereas that of the FIBs was reduced to 60% compared to their natural state on glass, leading to a faster migration rate of SCs than FIBs. The success of the complementary gradient relies on the appropriate interplay between the PDMAPS brushes and the cell-specific ligands, enabling the selective guidance of SCs migration.